Triton X-100 solubilized bone matrix-induced alkaline phosphatase - Pizauro, João M. [UNESP]; Curti, Carlos; Ciancaglini, Pietro; Leone, Francisco A. (Elsevier, 1987)
1. 1. Solubilized and membrane-bound alkaline phosphatase showed Michaelis-Menten behavior in a wide range of different substrate concentrations. 2. 2. Membrane-bound alkaline phosphatase has a molecular weight of 130,000 and its minimum active configuration comprises two identical subunits of about 65,000. 3. 3. The two forms of the enzyme behave similarly with respect to NaCl, urea and guanidine HCl. 4. 4. Catalytic groups have pK values of about 8.5 and 9.7 for both membrane-bound and solubilized enzyme. © 1987.
Keywords: alkaline phosphatase; detergent; macrogol derivative; octoxinol; animal; biosynthesis; bone matrix; cartilage; enzyme induction; enzyme specificity; enzymology; isolation and purification; kinetics; metabolism; molecular weight; physiology; rat; solubility; Alkaline Phosphatase; Animal; Bone Matrix; Cartilage; Detergents; Enzyme Induction; Kinetics; Molecular Weight; Octoxynol; Polyethylene Glycols; Rats; Solubility; Substrate Specificity; Support, Non-U.S. Gov't